Amputees Unanimous: A 12-step program. (June 2019) - Amorelli, Catrinna; Yancosek, Kathleen; Morris, Ruth
Background: Alongside physical impairment, psychosocial health issues may arise after amputation, impacting quality of life. Traditional psychosocial care models provide services in a linear fashion, with limited supports upon discharge. A novel program entitled Amputees Unanimous is a 12-step program provided for amputees by amputees. Objective: To shape the final content of Amputees Unanimous by identifying personal beliefs and opinions of healthcare professionals and amputees. Study Design: Qualitative design utilizing a phenomenological approach. Method: Five focus groups were held: four with amputees and one with healthcare providers. A phenomenological approach shaped the inquiry of the lived experience of limb loss in relation to the content of Amputees Unanimous. Results: Three themes emerged: (1) accepting limb loss, (2) peer inspiration, and (3) regaining prior level of function. Conclusion: Limb loss may alter one's self-image, both physically and psychologically, having a profound effect on how an individual copes throughout his or her lifetime. The content and delivery format of Amputees Unanimous could be tested for effectiveness as a program tailored to facilitate coping after limb loss and to provide encouragement, support, and hope for the future of amputees. Clinical relevance: A dynamic, amputee-led, mutual help program may provide individuals with limb loss a place for encouragement, support, and optimism for the future.